Antagonists of Calcium Fluxes and Calmodulin Block Activation of the p21-Activated Protein Kinases in Neutrophils - Lian, J.P. (Jian); Crossley, L. (Lisa); Zhan, Q. (Qian); Huang, R. (Riyun); Coffer, P.J.; Toker, A. (Alex); Robinson, D. (Dwight); Badwey, J.A. (John) (The American Association of Immunologists, 2000)
Neutrophils stimulated with fMLP or a variety of other chemoattractants that bind to serpentine receptors coupled to heterotrimeric G proteins exhibit rapid activation of two p21-activated protein kinases (Paks) with molecular masses of ~63 and 69 kDa (y- and a-Pak). Previous studies have shown that products of phosphatidylinositol 3-kinase and tyrosine kinases are required for the activation of Paks. We now report that a variety of structurally distinct compounds which interrupt different stages in calcium/calmodulin (CaM) signaling block activation of the 63- and 69-kDa Paks in fMLP-stimulated neutrophils. These antagonists included selective inhibitors of phospholipase C (1-[6-((17ß-3-methoxyestra-1,3,5(10)-trien-17-yl)amino)hexyl]-1H-pyrrole- 2,5-dione), the intracellular Ca^(2+) channel (8-(N,N-diethylamino)-octyl-3,4,5-trimethoxybenzoate), CaM (N-(6-aminohexyl)-5- chloro-1-naphthalenesulfonamide; N-(4-aminobutyl)-5-chloro-1-naphthalenesulfonamide; trifluoperazine), and CaM-activated protein kinases (N-[2-(N-(chlorocinnamyl)-N-methylaminomethyl)phenyl]-N-[2-hydroxyethyl]-4-methoxybenzenesulfonamide). This inhibition was dose-dependent with IC50 values very similar to those that interrupt CaM-dependent reactions in vitro. In contrast, less active analogues of these compounds (1-[6-((17ß-3-methoxyestra-1,3,5(10)-trien-17-yl)amino)hexyl]-2,5-pyrrolidinedione; N-(6-aminohexyl)-1-naphthalenesulfonamide; N-(4-aminobutyl)-1-naphthalenesulfonamide; promethazine; 2-[N-(4- methoxybenzenesulfonyl)]amino-N-(4-chlorocinnamyl)-N-methylbenzyl-amine]) did not affect activation of Paks in these cells. CaM antagonists (N-(6-aminohexyl)-5-chloro-1-naphthalenesulfonamide; trifluoperazine), but not their less-active analogues (N- (6-aminohexyl)-1-naphthalenesulfonamide; promethazine), were also found to block activation of the small GTPases Ras and Rac in stimulated neutrophils along with the extracellular signal-regulated kinases. These data strongly suggest that the Ca^(2+)/CaM complex plays a major role in the activation of a number of enzyme systems in neutrophils that are regulated by small GTPases.
Keywords: Geneeskunde